The Crime of Trafficking in Persons with the Mode of Becoming a Female Worker - Vicki Dwi Purnomo; Noor Rahmat (PT FORMOSA CENDEKIA GLOBAL, 2023)
Law enforcement against the criminal act of trafficking in persons with the mode of becoming a female worker occurs very often in Indonesia so this research was carried out using an empirical juridical research method because this research aims to determine law enforcement for female victims of trafficking in persons. Obstacles in law enforcement against female workers show: 1) Law enforcement against perpetrators of the crime of trafficking in persons with victims of labor is in accordance with applicable law. Even though in law enforcement against perpetrators and victims who have reconciled, the legal process is not at the level of the prosecutor's office (prosecution process). 2) The police as a law enforcement agency in the process of enforcing the law on the criminal act of trafficking in persons also considers the value of justice